Ilmu dan Ngelmu sebagai satu cara mencari pengetahuan - Noriah Mohamed,; Yusmilayati Yunos, (Universiti Kebangsaan Malaysia, 2009)
Although Ilmu (knowledge) and ngelmu (philosophy) may sound similar, they actually carry different definitions and this could be translated on the methods used to obtain each of them. Ilmu can be obtained from formal or informal education while ngelmu can be achieved through any practices that are related to Javanese spiritual concept. The characters of Ha Na Ca Ra Ka are based on someone’s understanding on life especially when they are communicating with God, human beings and also themselves. Self elements such as heneng, hening, and heling are vital in searching for ilmu and ngelmu. Besides that, they also need to possess some strong elements within themselves such as sabar (patience), pasrah (submit to their fate), nrima (acceptive) and rela (willingness). Although there are marginal Muslim Javanese in Indonesia, Islamic teachings can still be practiced according to their principles when they are out searching for ilmu and ngelmu, which are both derived from Allah the Almighty